2000
DOI: 10.5551/jat1994.7.91
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bezafibrate or Pravastatin on Serum Lipid Levels and Albuminuria in NIDDM Patients

Abstract: Lipid abnormalities in diabetic patients, particularly in those with nephropathy, may be partially due to deteriorating atherosclerosis. Therefore, strict control of the lipid metabolism in addition to glycemic control is desirable. Whether or not lipid lowering drugs prevent albuminuria in diabetic patients in the long term remains unclear. This study involved 71 NIDDM patients with hypercholesterolemia (group A: n = 37, group B: N = 34). The effect of bezafibrate (group A) or pravastatin (group B) on the cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…It is also of interest to note that bezafi brate reduced the LDL-C level after 24 h (Table I), but not after 7 h. Furthermore, other plasma lipid levels were not signifi cantly changed indicating that bezafi brate has an acute lowering activity only on plasma triglycerides and LDL-C. This is concomitant with the mechanism of action of fi brates (Fujiwara et al, 1997;Yamada, 1997;Norioka et al, 2000;Nagai et al, 2000;Hikita et al, 2000) whose LDL-C-lowering activity is not strongly marked, but their triglycerides-decreasing effect is very spectacular especially by stimulation of gene expression of lipoprotein lipase leading to enhanced catabolism of VLDL, synthesis of fatty acids and reduced VLDL secretion.…”
Section: Discussionmentioning
confidence: 60%
“…It is also of interest to note that bezafi brate reduced the LDL-C level after 24 h (Table I), but not after 7 h. Furthermore, other plasma lipid levels were not signifi cantly changed indicating that bezafi brate has an acute lowering activity only on plasma triglycerides and LDL-C. This is concomitant with the mechanism of action of fi brates (Fujiwara et al, 1997;Yamada, 1997;Norioka et al, 2000;Nagai et al, 2000;Hikita et al, 2000) whose LDL-C-lowering activity is not strongly marked, but their triglycerides-decreasing effect is very spectacular especially by stimulation of gene expression of lipoprotein lipase leading to enhanced catabolism of VLDL, synthesis of fatty acids and reduced VLDL secretion.…”
Section: Discussionmentioning
confidence: 60%
“…The evidence presented above provides a strong rationale for the use of pharmacological inhibitors of NADPH oxidase to combat oxidative stress and its associated vascular pathologies. The current research interest is to treat diabetic nephropathy by use of a fibrates class of interventions, such as fenofibrate, bezafibrate and gemfibrozil, well-known hypolipidemic agents [80][81][82] . Recently, in our laboratory we have shown that treatment with fenofibrate and concurrent administration of benfotiamine, a transketolase activator, prevented the development of diabetic nephropathy.…”
Section: Pharmacological Interventions To Treat Diabetic Smokers Withmentioning
confidence: 99%
“…6,7 Moreover, it has been shown that high levels of RLP-C are an independent risk factor for CV events in patients with type 2 diabetes mellitus. 12 We and others have shown that treatment with fibrates, including bezafibrate or gemfibrozil, effectively reduces RLP-C levels, 8,13, 14 and treatment with statins has also resulted in a significant reduction in RLP-C levels. 14, 15 However, those previous studies had small numbers of patients.…”
mentioning
confidence: 99%